CULTURAL MAPPING AS A TOOL IN HERITAGE CONSERVATION IN A WORLD HERITAGE SITE: THE VIGAN CITY EXPERIENCE - Rabang, Marie Rose Q. (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2015)
This paper presents how Vigan utilized cultural mapping as a tool in heritage conservation. It discusses the importance of cultural mapping and the process of documentation , the results of the hands-on cultural mapping activities in terms of documented resources, and the ensuing projects along heritage conservation that were adopted by the City Government of Vigan. The cultural mapping project covered four components of the heritage: natural heritage, built heritage, movable heritage and intangible heritage. The cultural mapping yielded ten volumes of documentation which were submitted to the local government of Vigan and were later exhibited at the University of Santo Tomas in Manila and at the Vigan Cultural Trade Center. Cultural heritage conservation projects ensued from the cultural mapping such as the Buridek: Vigan Children’s Museum, Vigan Heritage River Cruise and the UNESCO World Heritage City of Vigan Philippines Heritage Homeowner’s Preservation Manual. Keywords: 1. Cultural Mapping, 2. Cultural Heritage, 3. Heritage Conservation, 4.World Heritage Site, 5. Vigan City